Capture the wealth of heritage in a Holy City of Islam : the problem of developing tourism in Djenné in Mali - Diama Cissouma Togola; Soufian Al Karjousli (Via@)
The old town of Djenné was inscribed on the World Heritage List in 1988, which led to a boom in tourism. Since then, various development programmes have been proposed with the aim of preserving the architectural heritage of the mosque and traditional homes. These now form the links to intangible heritage which add to the richness of Djenné, including its relationship to Islam. It is sometimes difficult to make inhabitants’ expectations and respect for local values compatible with tourism and restoration projects. Only by taking into account the diversity in both tangible and intangible aspects of heritage, accompanied by a more equal redistribution of wealth, can tourism be allowed to develop in the context of sustainable development, leading to better living conditions for the population and the marginalization of radical Islam.